On the rocketship how top charter schools are pushing the envelope - Whitmire, Richard. (Jossey-Bass, 2014)
"Veteran journalist Richard Whitmire follows Rocketship through the school year and into the following year, when the nationally acclaimed charter school network launches new schools in Milwaukee. While Rocketship's story provides the narrative spine, the book also covers developments as other high quality charter organizations bid to reshape urban education in America. In 2012, charter school students made up only 5 percent of the total student population, but those numbers were growing fast and have huge impacts in the urban areas. As The New York Times recently pointed out, charter enrollment explains most of the enrollment declines in traditional schools in cities such as Chicago and Los Angeles.In this book, Whitmire will also explore one core innovation at Rocketship: its successful blended learning program. Rocketship's Learning Lab is where students spend two hours a day in computer-driven instruction powered by carefully selected software. This "blended learning" approach--Learning Lab blended with in-class instruction where teachers coordinate closely with the Lab--cuts expenses by 25 percent. Rocketship uses that extra money to fund longer school hours and higher teacher salaries. Today many schools around the country look to Rocketship as a model for using blended learning (many try to use blended learning, but few succeed)"-- |c Provided by publisher.